2017
DOI: 10.1098/rspb.2017.0208
|View full text |Cite
|
Sign up to set email alerts
|

Climatic niche evolution is faster in sympatric than allopatric lineages of the butterfly genusPyrgus

Abstract: Understanding how speciation relates to ecological divergence has long fascinated biologists. It is assumed that ecological divergence is essential to sympatric speciation, as a mechanism to avoid competition and eventually lead to reproductive isolation, while divergence in allopatry is not necessarily associated with niche differentiation. The impact of the spatial context of divergence on the evolutionary rates of abiotic dimensions of the ecological niche has rarely been explored for an entire clade. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 82 publications
3
18
0
Order By: Relevance
“…Our results partially agree with those of Pitteloud et al [85] in Pyrgus butterflies in which they found higher rates of niche evolution along climatic dimensions for sister lineages that diverge in sympatry. Haemulids are an ecologically diverse group of reef and shore fishes in the tropical Western Atlantic and the Eastern Pacific.…”
Section: Discussionsupporting
confidence: 93%
“…Our results partially agree with those of Pitteloud et al [85] in Pyrgus butterflies in which they found higher rates of niche evolution along climatic dimensions for sister lineages that diverge in sympatry. Haemulids are an ecologically diverse group of reef and shore fishes in the tropical Western Atlantic and the Eastern Pacific.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies highlighting the strength and ubiquity of isolation by environment (Sexton et al, ; Wang & Bradburd, ) have typically focused on finer scales, mostly at the level of recent population differentiation. Although some studies have demonstrated relatively high lability in environmental niche traits between closely related species (Peterson et al, ; Warren et al, ), few have demonstrated environmental niche divergence as a major factor promoting broader phylogeographic divergence or speciation (but see Cooney, Seddon, & Tobias, ; Pitteloud et al, ). Here, we find evidence for lineage diversification related to both geographic isolation and environmental niche evolution in an abundant and widespread lizard group that otherwise exhibits fairly strong niche and morphological conservatism.…”
Section: Discussionmentioning
confidence: 99%
“…Geography and ecology are always closely intertwined in speciation scenarios. There have been several studies that have investigated geographic range expansion in herbivorous insects (Becerra, Venable 1999;Slove, Janz 2011); climate induced host shifts (see Winkler, Mitter, Scheffer 2009;Nyman et al 2012 for reviews and recent studies since then Sanchez-Guillen et al 2016;Lisa De-Silva et al 2017;Owen et al 2017;Pitteloud et al 2017;Sahoo et al 2017) and climate driven diversification dynamics (Kergoat et al 2018, Letsch et al 2018.…”
Section: Iii1) Investigating the Role Of Abiotic Factors: Geography mentioning
confidence: 99%